ISO 10303 AP209—Why and how to embed nonlinear FEA. (April 2021) - Lanza, Remi; Haenisch, Jochen; Bengtsson, Kjell; Rølvåg, Terje
Highlights: STEP ISO 10303 AP209; a standard data format for FEA data. An investigation of the STEP ISO 10303 AP209 standard. Why and how to extend STEP ISO 10303 AP209 for nonlinear FEA. Improving data exchange of FEA information with STEP ISO 10303. Abstract: ISO 10303 STEP AP209 edition 2 ISO (1994), ISO (2014a)[1, 2] is a data model standard intended for data exchange and storage of simulation information. The standard has a wide coverage of FEA (Finite Element Analysis) information, but is missing certain features such as nonlinear FEA. This paper gives an introduction to the STEP AP209 standard and presents projects in which AP209 has been implemented. The study then identifies requirements that should be supported by a standard FEA data model, but are not fully covered by AP209. Each requirements are discussed in the context of how they are supported by existing major solver applications. Without giving detailed solutions for how these should be implemented in AP209, starting points for further research is suggested.